International Law against the risks of Artific ial Intelligence (AI) in human embryonic research - García San José, Daniel (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
For years, efforts have been made to achieve an internationally accepted ethical framework in relation to all applications and innovations of artificial intelligence (AI). The UNESCO Recommendation on the Ethics of AI, adopted in November 2021, is considered a milestone in this regard. In this paper we criticize the restrictive nature of the concept of human dignity used in this instrument for not protecting against the risks of using systems of artificial intelligence (AI) in human embryonic experimentation through synthetic wombs. We propose the establishment of a United Nations high commissioner for the responsible use of AI systems.